Brain Abscess and the Nonfenestrated Fontan Circulation - Runkel, Bethany G. (JACC Case Rep, 2020)
Brain abscess is a rare but life-threatening condition. Intracardiac or extracardiac right-to-left shunting in patients with unrepaired cyanotic congenital heart disease, pulmonary arteriovenous malformations, or venovenous collaterals allows microbes unfiltered access to the brain. Brain abscess must be considered when cyanotic patients present with headache. (Level of Difficulty: Beginner.)